Correlation analysis for screening key parameters for fish canning wastewater characterization - Cristovão, Raquel (2018)
A significant number of food industries do not have a proper wastewater treatment; fish canning is no exception, and the existing pre-treatment is insufficient, given the content of organic matter, oil and grease and salinity. In addition, this type of wastewaters shows high variability depending on the type of processes involved and effluent streams being discharged [1]. For this reason, its characterization is very important to conceive and implement the correct wastewater treatment layout. In this work, correlation analysis was used to identify the relationship between each wastewater parameter analyzed. Correlation coefficients between each parameter reflect their importance compared to others.